CONSTRUCTING AND VALIDATING A SCALE FOR ASSESSING THE SOCIABILITY OF TEACHERS - Snehalatha, SherineVinoca (International Journal of Research -GRANTHAALAYAH, 2016)
In the present context, educationist and education planners have started preferring social learning environments in the classrooms. Thus arises the need for teacher behaviour characteristically ‘sociable’ in nature. The ability to be in the company of others is the core of ‘sociability’. On analyzing literature, the author has identified three constructs forming the core of sociability – Trust and belonging; Sense of community; and Good working relationship. On the basis of these altogether 36 statements were formed to be answered on a 4 point scale ranging from Strongly Agree to Strongly Disagree. After establishing content validity, item validity, and construct validity, the draft tool retained thirty items. The presence of the trait constructs were established by confirmatory factor analysis. The rested reliability coefficient 0.697 upholds the consistency of the tool.